IMPLEMENTASI PEMBELAJARAN ASWAJA DALAM MENGEMBANGKAN PEMAHAMAN MODERASI BERAGAMA DI MTs MUNZALAM MUBAROKA BULUKERTO WONOGIRI - Amir Mukminin; Mustofa, Zamzam; Wahyuningtyas, Eka (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
This study aims to analyze the implementation of Aswaja learning in developing an understanding of religious moderation at MTs Munzalam Mubaroka. Based on observations, it was found that the Aswaja learning process has not yet achieved its optimal goals. Some students showed intolerance towards others' opinions during discussions and violated school regulations, such as not participating in pesantren orientation activities and lacking cooperation in group activities like community service. This research uses a qualitative approach with a case study method. The results indicate that students' knowledge of religious moderation is still low, as they have not received direct learning on the theory of moderation. However, through Aswaja learning, students are taught to be moderate in both religious and daily life practices. The Aswaja learning process includes the preparation of a syllabus, lesson plans (RPP), and the use of discussion, lecture, memorization, individual assignments, and storytelling methods. Learning evaluation is conducted through midterm (UTS) and final semester exams (UAS). In conclusion, although not yet fully optimal, Aswaja learning plays an important role in shaping students' attitudes toward religious moderation.